2017
DOI: 10.1039/c7ra09307a
|View full text |Cite
|
Sign up to set email alerts
|

Application of biochar-based catalysts in biomass upgrading: a review

Abstract: The application of biochars as versatile catalysts and/or catalyst supports for biomass upgrading is systematically overviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 102 publications
0
95
0
2
Order By: Relevance
“…For instance, the presence of inorganics such as K and Fe in biochar contributes to its catalytic activity for tar cracking [12]. The surface functional groups of biochar could facilitate the adsorption of metal precursors, a necessary step for the synthesis of biochar-supported metal catalysts [9,13,14]. On the other hand, some characteristics of biochar, such as a low surface area and a poor porosity, hamper its catalytic application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the presence of inorganics such as K and Fe in biochar contributes to its catalytic activity for tar cracking [12]. The surface functional groups of biochar could facilitate the adsorption of metal precursors, a necessary step for the synthesis of biochar-supported metal catalysts [9,13,14]. On the other hand, some characteristics of biochar, such as a low surface area and a poor porosity, hamper its catalytic application.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various modification strategies were developed to endow biochar with specific properties. These strategies include selecting proper feedstock, controlling synthesis conditions, physical or chemical activation [10,13], surface functionalization [14,15], forming composites with other materials [16], etc. Comprehensive reviews on this topic can be found in References [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis of biomass from waste streams has the potential of reducing fossil fuel usage due to the production of bio‐oil and syngas, and the capacity of mitigating global warming effects, since CO 2 is captured and stored as carbon in the form of biochar . The carbon‐rich solid produced by the pyrolysis of biomass under low oxygen concentrations and low temperatures defined as biochar has potential to be applied as a catalyst for reactions of CO 2 because it is porous and contains easily tuned surface functionality due to the presence of abundant functional groups . Treatment of biochar and carbon‐based materials with nitric acid (HNO 3 ) is known to greatly increase the content of oxygenated groups on their surface, introducing more hydroxyl and carboxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The carbon-rich solid produced by the pyrolysis of biomass under low oxygen concentrations and low temperatures defined as biochar has potential to be applied as a catalyst for reactions of CO 2 because it is porous and contains easily tuned surface functionality due to the presence of abundant functional groups. [21,22] Treatment of biochar and carbon-based materials with nitric acid (HNO 3 ) is known to greatly increase the content of oxygenated groups on their surface, [22][23][24][25] introducing more hydroxyl and carboxyl groups. These functional groups are important structural motifs in catalysts for the reaction chosen herein.…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous carbon obtained by incomplete carbonization of carbohydrate is a kind of soft carbon possessing polycyclic aromatic carbon sheets in a three-dimensional sp 3 -bonded structure [30,31]. After sulfonation, this amorphous carbon could generate a stable solid acid catalyst with abundant sulfonic sites, which has been reported to effectively catalyze the esterification of fatty acids to produce biodiesel [32][33][34]. So far, there has been no report about its utilization in esterification of LA to produce fuel additives.…”
Section: Introductionmentioning
confidence: 99%